Modelling the cost-effectiveness of introducing rapid syphilis tests into an antenatal syphilis screening programme in Mwanza, Tanzania. (10th January 2007) - Vickerman, P; Peeling, R W; Terris-Prestholt, F; Changalucha, J; Mabey, D; Watson-Jones, D; Watts, C
Abstract : Objectives: A study found screening (with rapid plasma reagin (RPR)) pregnant women for maternal syphilis was cost-effective in Mwanza, Tanzania. Recently, four rapid point-of-care (POC) syphilis tests were evaluated in Mwanza, and found to have reasonable sensitivity/specificity. This analysis estimates the relative cost-effectiveness of using these POC tests in the Mwanza syphilis screening intervention. Methods: Empirical cost and epidemiological data were used to model the potential benefit of using POC tests instead of RPR. Reductions in costs relating to training, supplies, and equipment were estimated, and any changes in impact due to test sensitivity were included. Additional modelling explored how the results vary with prevalence of past infection, misclassified RPR results, and if not all women return for treatment. Results: The cost-effectiveness of using POC tests is mainly dependent on their cost and sensitivity for high titre active syphilis (HTAS). Savings due to reductions in training and equipment are small. Current POC tests may save more disability-adjusted life years (DALYs) than the RPR test in Mwanza, but the test cost needs to be <US$0.63 to be as cost-effective as RPR. However, the cost-effectiveness of the RPR test worsens by 15% if its HTAS sensitivity had been 75% instead of 86%, and by 25–65% if 20–40% of women had not returned for treatment. In such settings, POC tests could improve cost-effectiveness. Lastly, the cost-effectiveness of POC tests is affected little by the prevalence of syphilis, false RPR-positives, and past infections. Discussion: Although the price of most POC tests needs to be reduced to make them as cost-effective as RPR, their simplicity and limited requirements for electricity/equipment suggest their use could improve the coverage of antenatal syphilis screening in developing countries.